Mechanism of chromatin segregation to the nuclear periphery in C. elegans embryos. Issue 3 (2nd July 2016) - Gonzalez-Sandoval, Adriana; Gasser, Susan M.
ABSTRACT: In eukaryotic organisms, gene regulation occurs in the context of chromatin. In the interphase nucleus, euchromatin and heterochromatin occupy distinct space during cell differentiation, with heterochromatin becoming enriched at the nuclear and nucleolar peripheries. This organization is thought to fine-tune gene expression. To elucidate the mechanisms that govern this level of genome organization, screens were carried out in C. elegans which monitored the loss of heterochromatin sequestration at the nuclear periphery. This led to the identification of a novel chromodomain protein, CEC-4 ( Caenorhabditis elegans chromodomain protein 4) that mediates the anchoring of H3K9 methylation-bearing chromatin at the nuclear periphery in early to mid-stage embryos. Surprisingly, the loss of CEC-4 does not derepress genes found in heterochromatic domains, nor does it affect differentiation under standard laboratory conditions. On the other hand, CEC-4 contributes to the efficiency with which muscle differentiation is induced following ectopic expression of the master regulator, HLH-1. This is one of the first phenotypes specifically attributed to the ablation of heterochromatin anchoring.